2023
DOI: 10.1159/000533609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medical and Surgical Obesity Treatment on Dental Caries: A 2-Year Prospective Cohort Study

Negin Taghat,
Karin Mossberg,
Peter Lingström
et al.

Abstract: The objective was to study the long-term effects on oral health of bariatric surgery compared with medical treatment of obesity. Swedish females with morbid obesity (n = 66;18-35 years at baseline) were followed prospectively from before obesity treatment until two years after treatment. The main response variable was dental caries registered according to the ICDAS-II system. Possible confounding caused by sociodemographic characteristics, general health, oral health habits and oral hygiene was controlled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The present study is in line with research that also recommends periodic prophylaxis to help improve the oral hygiene status of patients undergoing bariatric surgery, which results in the prevention of oral diseases such as periodontitis, thus greatly improving the patient’s quality of life 20 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The present study is in line with research that also recommends periodic prophylaxis to help improve the oral hygiene status of patients undergoing bariatric surgery, which results in the prevention of oral diseases such as periodontitis, thus greatly improving the patient’s quality of life 20 .…”
Section: Discussionsupporting
confidence: 86%
“…After six and 12 months, the incidence of caries was significantly lower among members of the IG compared to those in the CG, both in enamel and dentin. A previous study, in which there was no dental intervention, reported a significant increase in dental caries over time following gastroplasty 20 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations